Income and religion: a heterogeneous panel data analysis - Sequeira, T. N.; Viegas, R.; Ferreira-Lopes, A. (Review of Social Economy, 2017)
A recent empirical literature has addressed the relationship between income and religion, but most of the studies are based on microdata. Macroeconomic analysis of the issue has largely ignored the potential heterogeneity between countries. Using retrospective data on church attendance rates for a panel of countries between 1925 and 1990, we apply heterogeneous panel data estimators and reveal that the effect of participation in religious activities on income per capita is mostly non-significant. This is consistent with some of the recent research that casts doubt onto the influence of religion on income, once causality is taken into account.